PERTUMBUHAN TANAMAN KENARI (Canarium ambonensis) DI DEMPLOT SUMBER BENIH HATUSUA KABUPATEN SERAM BAGIAN BARAT - Ludia Siahaya; C.M.A Wattimena; Jacobs Harry A (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2020)
The aim of this research was to know the level of growth of high and diameter increament of Kenari plant (Canarium ambonensis) for 3.5 years after planting, to know the relationship between pH and Kenari plant growth (C. ambonensis), and to know the relationship between soil moisture with Kenari plant growth (C. ambonensis). Method used was observation and measurement high, diameter, pH and moisture of soil at 100 of Kenari plant. Then, acoounting Current Annual Increatmnet (CAI), Mean Annual Increatmnet (MAI) value and Simple Regretion to show correlation between pH and moisture of soil with growth of Kenari plant. The results of the study showed value of diameter CAI and MAI were 2.26 cm/plant/year and 1.41 cm/plant/year, and value of high CAI and MAI were 1.72 m/plant/year and 0.97 m/plant/year. The relationship of soil pH and humidity with the growth of Kenari (Canarium ambonensis) can contribute very low.